Clinical implementation of next-generation sequencing in tertiary health system: the Rijeka retrospective study - Nina Pereza; Sanja Dević Pavlić; Tea Mladenić; Željka Hrupački; Dorotea Vukelić Drašković; Luca Lovrečić; Aleš Maver; Jadranka Vraneković; Iva Bilić Čače; Igor Prpić; Ivona Butorac Ahel; Vladimira Vuletić; et al. (Frontiers in Genetics, 2026)
Objective This study aimed to assess the diagnostic yield, clinical indications, and utility of next-generation sequencing (NGS) testing since its implementation through collaboration between the University of Rijeka Faculty of Medicine and the Clinical Hospital Centre Rijeka. Materials and Methods This retrospective study included patients referred between 2018 and 2023 from the Clinical Hospital Centre Rijeka to the University of Rijeka Faculty of Medicine for genetic testing, primarily using exome sequencing. Results Between April 2018 and December 2023, 412 patients were referred for exome sequencing, of whom 353 (85.7%) underwent diagnostic genetic testing. A notable increase in tests ordered was observed over time. Patients were most frequently referred from Pediatrics (55.0%), Neurology (29.5%), Cardiology (7.4%), Ophthalmology (3.4%), and others (4.7%). A diagnosis was confirmed in 103/353 patients, corresponding to an overall diagnostic yield of 29.2%, and an adjusted diagnostic yield of 27.2% after collapsing related individuals into single family units. In these confirmed cases, 83 distinct disorders involving 71 unique genes were identified, with most patients showing heterozygous variants and several recurrent disorders and genes. Variants of uncertain significance were reported in 35/353 (9.9%) patients. Conclusion The 27.2% diagnostic yield demonstrates effective integration of NGS into tertiary clinical practice. The recent introduction of medical genetics specialization is expected to further improve referral quality, variant interpretation, and overall diagnostic outcomes.